The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1042/etls20200331
|View full text |Cite
|
Sign up to set email alerts
|

Affinity maturation: highlights in the application of in vitro strategies for the directed evolution of antibodies

Abstract: Affinity maturation is a key technique in protein engineering which is used to improve affinity and binding interactions in vitro, a process often required to fulfil the therapeutic potential of antibodies. There are many available display technologies and maturation methods developed over the years, which have been instrumental in the production of therapeutic antibodies. However, due to the inherent limitations in display capacity of these technologies, accommodation of expansive and complex library builds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The resulting antibodies can be highly mutated compared to their germline-encoded counterparts, with the affinity for antigens being significantly increased compared to the corresponding naïve B cell receptors [ 55 , 56 ]. This makes affinity maturation a key technique in protein engineering to improve affinity and binding interactions in vitro in order to optimize the therapeutic potential of antibodies [ 57 ]. Adler et al observed that in vivo affinity-matured antibodies predominantly accumulate mutations within the CDR3 regions, with a total of 6–7 amino acid changes in the heavy and light chain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting antibodies can be highly mutated compared to their germline-encoded counterparts, with the affinity for antigens being significantly increased compared to the corresponding naïve B cell receptors [ 55 , 56 ]. This makes affinity maturation a key technique in protein engineering to improve affinity and binding interactions in vitro in order to optimize the therapeutic potential of antibodies [ 57 ]. Adler et al observed that in vivo affinity-matured antibodies predominantly accumulate mutations within the CDR3 regions, with a total of 6–7 amino acid changes in the heavy and light chain [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies undergo affinity optimization before they can be considered potential therapeutic drugs [ 8 ]. Techniques such as site-directed mutagenesis, chain shuffling, and error-prone PCR are commonly utilized for antibody affinity maturation [ 9 , 10 ]. However, this process is often time-consuming, spanning several months.…”
Section: Introductionmentioning
confidence: 99%
“…However, this daunting task of enhancing the affinity using in vitro methods is rather complicated, expensive, and time-consuming. Structure-based computational engineering offers an attractive alternative strategy for the development of biotherapeutic antibodies [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%